Sosialisasi dan Penguatan Kesadaran Masyarakat terhadap Sertifikat Halal Di Desa Karang Gading, Kec. Secanggang, Kab. Langkat - Rispan Efendi Lubis; Anita Khairunnisa; Muhammad Fery Prayoga; Wendi Setiawan; Fajar Husin (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Halal certification is an important instrument to ensure product compliance with Islamic law, provide consumer protection, and increase the competitiveness of micro and small enterprises (MSEs). However, the literacy level of the community in Karang Gading Village, Secanggang District, regarding halal certification is still relatively low. This condition results in most food business actors not having halal certification and do not understand the application procedures, potentially hindering market access and consumer trust in their products. This community service activity aims to increase the understanding, awareness, and readiness of the community, especially MSEs, in managing halal certification and encourage compliance with Halal Product Guarantee regulations. This community service activity aims to increase the understanding, awareness, and readiness of the community, especially MSEs, in managing halal certification and encourage compliance with Halal Product Guarantee regulations. The method used is an educational-participatory approach through preparation stages, material preparation, outreach seminars, interactive discussions, guidance on halal certificate registration procedures, and activity evaluation. The activity was attended by 22 participants consisting of MSEs, village officials, students, and community representatives. The analysis technique used is descriptive qualitative analysis based on the results of observations, discussions, participant participation, and feedback obtained during the activity. The results of the activity demonstrated an increase in participants' understanding of the halal concept, the benefits of halal certification, administrative requirements, and the stages of applying for halal certification. The participants' enthusiasm was evident in the high level of participation in the discussion and consultation sessions. Furthermore, most participants expressed their commitment to immediately applying for halal certification for their products. This activity contributes to improving regulatory compliance, strengthening consumer trust, and supporting local economic development by increasing the competitiveness of MSE products.